Pain،analgeasic،Doum palm،anxie Evaluation of Anxiolytic and Antidepressant Activities of aqueous and Methanolic extract of Hyphaene thebaica (doum) fruit in Animal Models (مجلة البحوث الأكاديمية, 2025)
Hyphaene thebaica (HT), also known as the "Doum palm" belonging to family Aceraceae, is a palm tree native to Africa. Aims: The current study sought to evaluate the anxiolytic-like activities, antidepressant, analgesic and properties of (DPME) and (DPAE) in stressed mice. Experimental design: The study was experimental research designed to include four lines: extraction of the plant materials, evaluation of anxiety using three tests: HCT, OFT, and LDBT, while the depressant activity is assessed by TST. The efficacy of the DPME and DPAE-mediated antidepressant and anxiolytic activities was compared with the control groups, diazepam (1 mg/kg, i.p) as an anxiolytic drug, and fluoxetine (20 mg/kg, p.o.) as an antidepressant drug evaluation of peripheral analgesic activities of DPME and DPAE using the chemical method (acetic acid 1%, i.p.). The fourth line was an assessment of the effect of DPME on PILO (280 mg/kg)-induced convulsions. The study was carried out using Albino mice (30±5 g) of either sex, which were divided into several groups with six mice each.
Keywords: Pain; analgeasic; Doum palm; anxiety; Mitodepressant